Acoustic data from IESSNS north, northeast, and south of Iceland in July 2020 - Ólafsdóttir, Anna H; Pampoulie, Christophe (PANGAEA, 2025)
This data set has acoustic data during the Icelandic part of the International Ecosystem Summer Survey in Nordic Seas (IESSNS) July 1-30, 2020. The survey area was the shelf, shelf edge and deeper waters north, northeast, and south of Iceland, including over the Reykjanes Ridge and into the southern part of the Irminger Sea. The acoustic data was collected using a Simrad EK80 scientific echo sounder transducer with five transceiver units operating at different frequencies which are 18 kHz, 38 kHz, 70, kHz, 120 kHz and 200 kHz. Sampling depth is measured from transceiver surface which is located at 9 m depth in the water column. Maximum sampling depth ranged from 500 m to 750 m. The echo sounder was calibrated prior to survey as per manufacturer's instructions and a calibration file is included with submission, called calibration_2020.xml. Raw power (W), number of transducer segments and transceiver impedance (Ohm) were recorded. Information about the trawl catches and biological measurement of catch collected during the survey is in data set Ólafsdóttir and Pampoulie (2021, doi:10.1594/PANGAEA.930437). For detailed information about the survey see the survey report (Ólafsdóttir et al., 2020).
Keywords: acoustic data; IESSNS; July 2020; Northeast Atlantic